Bridging Informal and Formal HRM Systems in Coastal Economies: A Systematic Literature Review of Workforce Transformation in Marine Sectors - Wulandari Dyah Pitaloka; Muhammad Abdul Latif (Journal of Idealistic Human Resources, 2025)
Objective: This study aims to examine the transformation of Human Resource Management (HRM) in the maritime sector by identifying how Digital Human Resource Management (D-HRM), Sustainable HRM, and Eco-friendly HRM function as bridging mechanisms in the transition from an informal labor system toward a formal, sustainable, and technology-driven maritime labor governance system within the context of the blue economy. Research Design & Methods: This study employs a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Data were collected from the Scopus, Web of Science, and ScienceDirect databases, covering publications from 2018 to 2025. A total of 37 Q1-indexed journal articles were analyzed using qualitative synthesis and VOSviewer bibliometric mapping. Findings: The results show an upward trend in maritime HRM research after 2020, particularly regarding issues of digitalization and sustainability. Human resource management has emerged as a central theme related to sustainability, fisheries, and decision-making. This study also found that Digital HRM supports workforce formalization, while Sustainable and Green HRM strengthens workforce resilience and organizational sustainability in the maritime sector. Implications & Recommendations: Maritime organizations and policymakers need to develop inclusive digital HR systems, strengthen workforce upskilling, and integrate sustainability principles into maritime labor governance. Contribution & Value Added: This study positions Human Resource Management (HRM) as a strategic bridging mechanism connecting workforce transformation, sustainability, and institutional adaptation in the maritime sector.